Isolation of Clostridioides difficile from different outdoor sites in the domestic environment. (April 2020) - Janezic, Sandra; Smrke, Julija; Rupnik, Maja
Abstract: Clostridioides difficile was isolated from 12 of 25 samples collected from the gardens of five individual houses and 132 isolates belonged to 12 PCR ribotypes. Compost material had the highest positivity rate and the highest PCR ribotype diversity in comparison to soil from vegetable and flower gardens. Isolated PCR ribotypes overlap with common human and animal types but also with divergent C. difficile lineages common for the soil environment. Graphical abstract: Image 1 Highlights: C. difficile could be isolated from in the garden soil and compost sites of the individual houses. Compost piles are the site with higher contamination rate and the highest diversity of PCR ribotypes. A considerable proportion of isolated PCR ribotypes belong to divergent C. difficile lineages.